Infecciones recurrentes asociadas a la atención de salud en pacientes posquirúrgicos cardiacos en la unidad de cuidados intensivos - Andino Pilco, Patricia Alexandra (2025)
Background: Recurrent health care-associated infections occupy about 10% approximately of all hospitalizations, thus causing a serious problem for public health worldwide. The objective was to identify the factors that cause recurrent health care-associated infections in post-cardiac surgery patients in the intensive care unit. Methods: A qualitative and descriptive literature review was carried out, using articles from journals indexed in databases such as Scielo, PubMed, and others, with specific inclusion criteria to ensure the quality and relevance of the information. Results: revealed a complex network of risk factors for these infections, including patient characteristics (female sex, diabetes, obesity), factors related to the surgical procedure (prolonged intubation times, significant blood loss), and the presence of multidrug-resistant organisms. Several types of postoperative infections were identified, the most common being surgical site infections, ventilator-associated pneumonia, urinary tract infections, and bloodstream infections. The most frequent pathogens included Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Escherichia coli, among others. Prevention strategies highlighted in the study included preoperative interventions, antibiotic prophylaxis and intraoperative techniques. Conclusions: The review concluded that the prevention and management of these infections requires a holistic approach that considers both the optimization of the patient's health status and the implementation of rigorous infection control protocols.